Jumping through hoops: An overview of the experiences and perspectives of Aboriginal mothers involved with child welfare in Manitoba - Bennett, Marlyn; Spillett, Leslie; Dunn, Catherine (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2012)
This article provides an overview of the experiences of Aboriginal mothers involved with child welfare in Manitoba. Jumping through hoops was a prominent perspective evident in stories and reflections that Aboriginal mothers shared about their experiences with child welfare and legal systems. The research drew upon interviews and talking circles conducted with Aboriginal women, and included interviews conducted with community advocates and lawyers in the spring and summer of 2007.